(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The present research focuses on social skills in a workplace. In this article, we propose an elaborate way to identify and collect social skills observed in situ in the innovative context of labor-union negotiations. This methodological system includes the creation of specific tools, observations in real situations, films and some interviews such as self-confrontations. Results demonstrate that the proposed method dynamically integrates various steps designed to expose the existence of social skills in a developmental context with challenging and sometimes conflicting issues. Identifying the essential social skills in labor-union negotiation allows consideration of the place of vocational training in the development of these skills in negotiation situations and, more widely, in the field of social dialogue.